Microstrip hybrid wideband 10 dB coupler - Indžić, Mustafa; Imeci, Sehabeddin Taha (Sustainable Engineering and Innovation, 2021)
In this paper, the design, simulation, optimization and testing of a Microstrip Hybrid 10 dB Wideband Coupler was done. The aim of the project was to introduce a new coupler design and to achieve stable operation for as wide bandwidth as possible. For this proposed design simulated results are as follows: 3.8 GHz Bandwidth and Coupling Amplitude balance of 1 dB across it. Coupler is then produced using LPKF ProtoMat 104s machine and it is tested with Vector Network Analyzer at Istanbul Technical University.